Painpresntations in children - Ashraf Ahmed Mohamed; Ekramy Mansour Abdelghfar; Salah Eldin Ahmed Ibrahim; Somaya Mansour Abdelgwad (Cairo : Ashraf Ahmed Mohamed, 2012)
Pain in children had not been treated well in the past , due to a lot of myths but , in the last two decads , a lot of facts were detected about pain in children in this essay , a lot of these facts has been discussed along with exploration of a lot of myths in the introduction , neurodevelopment of pain in children was discussed , followed by pain measurment in children then , the type of pain acute and chronic was reviewed then the management of pain in children was decleard
Thesis (M.Sc.) - Cairo University - National Cancer Institute - Department of Anaesthesia and pain Relief
Issued also as CD
Keywords: Pain; Pain measurement; Pain presentation in children